Europejska Strategia Bezpieczeństwa 2003–2008. Analiza politologiczna - Czachór, Zbigniew (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
In 2003, the Council of Europe, the highest political organ of the European Union, resolved to adopt the European Security Strategy. This document outlined three fundamental objectives for the EU: stability and good governance in the area of the EU’s closest neighbors; creating an international order that would be based not only on bilateral relations, but primarily on efficient multilateral relations; and preventing threats, whether new or traditional. The Strategy assumed that the EU would take the responsibility for international security both in the realm of ‘peace keeping’ (peace and defensive missions) and ‘peace-making’ (peace and offensive missions). Defining the threats that the European Union needs to defy, the Strategy enumerates local conflicts, terrorism, the proliferation of weapons of mass destruction and their potential use against the territory of the EU and its member states, collapsing states, and conflicts breaking out in such states and their neighborhood, as well as organized crime. The assessment of numerous threats to internal and external security, presented in the European Security Strategy, remains up-to-date. There have also emerged new threats for Europe that result from the need to ensure energy security, primarily with respect to the diversification of energy sources. The significance of climate change to international security has increased. The same applies to IT security or piracy. The EU has been rather anxious about the intensification of frozen conflicts, in particular the outbreak of war between Russia and Georgia. The Polish Ministry of Foreign Affairs has indicated that the enlargement process is a significant stabilizing factor in the EU neighborhood. Fundamental importance is also attached to the review of cooperation principles with the USA, the crucial role of the UN in the international system, and cooperation with regional organizations, such as the African Union. There is also the need to develop a strategic partnership with NATO, in particular in terms of operational cooperation. Another key factor in the strengthening of the EU’s global position is the development of a civil and military crisis response system.